FEMALE PROMISCUITY AND MATERNALLY DEPENDENT OFFSPRING GROWTH RATES IN MAMMALS. (1st April 2014) - Garratt, Michael; Brooks, Robert C; Lemaître, Jean‐François; Gaillard, Jean‐Michel
Abstract: Conflicts between family members are expected to influence the duration and intensity of parental care. In mammals, the majority of this care occurs as resource transfer from mothers to offspring during gestation and lactation. Mating systems can have a strong influence on the severity of familial conflict—where female promiscuity is prevalent, conflict is expected to be higher between family members, causing offspring to demand more resources. If offspring are capable of manipulating their mothers and receive resources in proportion to their demands, resource transfer should increase with elevated promiscuity. We tested this prediction, unexplored across mammals, using a comparative approach. The total durations of gestation and lactation were not related to testes mass, a reliable proxy of female promiscuity across taxa. Offspring growth during gestation, however, and weaning mass, were positively correlated with testes mass, suggesting that offspring gain resources from their mothers at faster rates when familial conflict is greater. During gestation, the relationship between offspring growth and testes mass was also related to placenta morphology, with a stronger relationship between testes mass and growth observed in species with a less invasive placenta. Familial conflict could have a pervasive influence on patterns of parental care in mammals.